Prevalence of depression among patients with type 2 diabetes mellitus: a cross-sectional study - Parihar, Sanjay; Singh, Rajesh (International Journal of Advances in Medicine, 2019)
Background: Depression can be viewed as a modifiable independent risk factor for the development of T2DM and for progression of complications from either type 1 or type 2 diabetes. The recognition and addressal of this association can have profound implications for prevention and treatment of these disorders. Objectives of this study the prevalence of depression among patients with diabetes mellitus type 2. Methods: A semi-structured questionnaire was used to collect the sociodemographic profile and the details of the diabetes and its treatment and history of other chronic diseases. Beck depression inventory (BDS-II) was used for evaluation of depression and 8 item Morisky medication adherence scale (MMAS-8) was used for measurement of patient’s adherence to medication. Results: Majority of the potential cases of depression (33%) were in the age group of 51-60 years. 62% of the patients were male. Majority of the patients (40%) were in the age group of 51-60 years. 73.4% of the married patients were potential cases of depression. 78% of the patients were having family history of type 2 diabetes mellitus. Majority of the patients (72%) were overweight or obese (BMI> 25kg/m2). Conclusion: Duration of diabetes and duration of treatment was 5-10 years in majority of the patients and were significantly associated with prevalence of depression. Prevalence of depression was associated with sex, religion, and family history but was not statistically significant.